Bacterial Community and Fermentation Quality of Ensiling Alfalfa With Commercial Lactic Acid Bacterial Additives - Na, Na; Qili, Moge; Wu, Nier; Sun, Lin; Xu, Haiwen; Zhao, Yi; Wei, Xiaobin; Xue, Yanlin; Tao, Ya (Frontiers in Microbiology, 2022)
The aim of this study was to determine the effects of six common commercial lactic acid bacteria (LAB) additives [A1, Lactobacillus plantarum, L. buchneri, and Enterococcus faecalis; A2, L. plantarum and L. casei; A3, L. plantarum and L. buchneri; A4, L. plantarum, L. buchneri, L. casei, and Pediococcus acidilactici; A5, L. plantarum (producing feruloyl esterase); and A6, L. buchneri, P. acidilactici, β-glucanase, and xylanase] on the bacterial community and fermentation quality of alfalfa silage. Alfalfa was harvested at the squaring stage, wilted in the field for 24 h, and ensiled without any additives (Control) or with A1, A2, A3, A4, A5, or A6. Microbial counts, bacterial community, fermentation parameters, and nutritional composition were determined after ensiling for 90 days. The total abundance of LAB genera on alfalfa pre-ensiling was 0.38% in bacterial community. The abundances of Lactobacillus, Enterococcus, and Pediococcus in the Control silage were 42.18, 40.18, and 8.09% of abundance, respectively. The abundances of Lactobacillus in A1-, A2-, A3-, A4-, and A5-treatments were 89.32, 92.93, 92.87, 81.12, and 80.44%, respectively. The abundances of Pediococcus and Lactobacillus in A6-treatment were 70.14 and 24.86%, respectively. Compared with Control silage, LAB-treated silage had lower pH and less ammonia nitrogen and water-soluble carbohydrates concentrations (p < 0.05). Further, the A5- and A6-treatments contained lower neutral detergent fiber, acid detergent fiber, and hemicellulose than other treatments (p < 0.05). Overall, LAB genera were presented as minor taxa in alfalfa pre-ensiling and as dominant taxa in alfalfa silage. Adding LAB additives improved the fermentation quality and altered the bacterial community of alfalfa silage. The main bacterial genera in Control silage were Lactobacillus, Enterococcus, and Pediococcus. Lactobacillus dominated the bacterial communities of A1-, A2-, A3-, A4-, and A5-treatments, while Pediococcus and Lactobacillus were dominant bacterial genera in A6-treatment. Inoculating A5 and A6 degraded the fiber in alfalfa silage. It is necessary to ensile alfalfa with LAB inoculants.